Assessment of Trace Metals Concentration in Tree Barks as Indicator of Atmospheric Pollution within Ibadan City, South-West, Nigeria - Ikechukwu P. Ejidike; Percy C. Onianwa (Journal of Analytical Methods in Chemistry)
Tree bark species were randomly collected from 65 sites having different anthropogenic activities, such as industrial, high traffic commercial, residential high and residential low traffic volume areas of Ibadan City, Nigeria. Levels of Cd, Cu, Pb, Zn, Co, and Cr of the dry-ashed bark samples were determined by AAS. The mean metal concentrations (mg kg−1) in samples from industrial zone were found as Pb: 3.67±1.97, Cd: 0.10±0.07, Zn: 30.96±32.05, Cu: 7.29±5.17, Co: 0.91±0.58, and Cr: 2.61±1.84. The trend of mean trace metal concentrations at high traffic commercial zone follows the order: Zn > Pb > Cu > Cr > Co > Cd. Residential high traffic and low traffic zones revealed the same trend as Cd < Co < Cr < Pb < Cu < Zn. Relatively strong positive correlation between the heavy metals at ρ<0.05, such as Zn versus Cu (r=0.79) and Co versus Cu (r=0.77), was observed. The results of the study suggest that tree bark samples could potentially serve as bioindicators for Cu, Pb, Zn, Cr, and possibly Co and Cd. Furthermore, interspecies variation of heavy metal concentrations in plants barks is recommended.